Kinematic Analysis of Lumbar Spine Depending on Three McKenzie’s Extension Exercises in Prone - Bo, Gak Hwang; Park, So Hyun (Journal of Physical Therapy Science, 2012)
[Purpose] This study was conducted to compare three McKenzie’s extension exercises in the prone position using kinematic analysis with fluoroscopy. [Subjects and Methods] Twelve healthy females without a history of low back pain participated. Lumbosacral lordorsis, intervertebral body angle, anterior heights of intervertebral disc and intervertebral body displacement were measured in three exercises: prone lying, prone lying on elbows, prone press-up. [Results] Prone press-up had a significantly higher value of lumbosacral lordosis than prone lying on elbows and prone lying (p<0.05). The intervertebral body angle and anterior height of the intervertebral disc at L3/4 were significantly higher in prone lying on elbows and prone press-up than in prone lying (p<0.05). There were significant differences among all exercises at L4/5 in the anterior height of the intervertebral disc(p<0.05), and a significantly higher value in prone press-up than in prone lying or prone lying on elbows at L5/S1 (p<0.05). However, there was no significant difference in intervertebral body displacement (p>0.05). [Conclusion] These findings suggest that prone lying on the elbows might be effective at treating disc bulging at the cephalic level and that prone press-ups are effective for treatment of relatively caudal lumbar disc pathology. Our study provides normative reference values for treating low back pain during McKenzie’s exercise.